Perubahan Beragama Dan Budaya Akibat Virus Covid-19 Ditinjau Dari Pendekatan Antropologi - Jagat Rayana; Mustopa; Ulummudin (Cakrawala: Journal of Religious Studies and Global Society, 2024)
In 2020, Covid-19 occurred which caused panic, fear, anxiety and various other excessive expressions in society. This is due to differences in background, religion, education, personality and individual perceptions of society which of course are also different. The purpose of this study examines the concept of an anthropological approach, how the Covid-19 pandemic is when studied from an anthropological perspective and what kind of new culture is formed during this pandemic. This research is included in qualitative research with a descriptive approach method to explain facts, data and research objects. This research was conducted at the Muhajirin Mosque, Perum Tamanjaya, Tasikmalaya City and residents as data reinforcement. Meanwhile, research data was collected through three techniques, namely observation, interviews and documentation. The results of the study show that the evolution of religion and culture that occurred due to the Covid-19 pandemic in Tasikmalaya City included restrictions on religion such as congregational prayers, religious studies and grand tablighs that have been tightened and even stopped. Likewise, the culture of going home, silaturahmi, shaking hands and other cultures have also been stopped and replaced virtually. The impact of the changes that have occurred has given rise to various expressions among the community and anthropology as an approach that studies humans and all their behavior tries to understand the various differences that have occurred due to the Covid-19 pandemic.